2021
DOI: 10.18316/sdh.v9i2.7216
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento multiprofissional da obesidade sobre o risco cardiometabólico e a aptidão física relacionada à saúde de mulheres com obesidade severa

Abstract: Objetivos: Analisar os efeitos de um programa multiprofissional de tratamento da obesidade (PMTO) sobre o risco cardiometabólico e a aptidão física relacionada à saúde (AFRS) de mulheres com obesidade severa. Materiais e Métodos: Participaram deste ensaio clínico pragmático 12 mulheres de um PMTO com 24 semanas incluindo prática de exercícios físicos, orientações de educação física, nutrição e psicologia. Resultados: Houve melhora significante em todos os parâmetros antropométricos, de composição corporal, da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Participants were selected to take part in the research project during the years 2018, 2019, 2020 (first semester), and 2022 (second semester) through the Multidisciplinary Treatment of Obesity Program (MTOP) coordinated by the Multidisciplinary Obesity Studies Nucleus (NEMO) of the State University of Maringá (UEM) and Regional University Hospital of Maringá (HUM). A detailed description of this study can be found elsewhere [ 15 ]. In brief, eligible participants were invited to take part voluntarily in the study through dissemination in the local media (TV, radio, newspaper) and social networks (website and institutional email, Facebook).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were selected to take part in the research project during the years 2018, 2019, 2020 (first semester), and 2022 (second semester) through the Multidisciplinary Treatment of Obesity Program (MTOP) coordinated by the Multidisciplinary Obesity Studies Nucleus (NEMO) of the State University of Maringá (UEM) and Regional University Hospital of Maringá (HUM). A detailed description of this study can be found elsewhere [ 15 ]. In brief, eligible participants were invited to take part voluntarily in the study through dissemination in the local media (TV, radio, newspaper) and social networks (website and institutional email, Facebook).…”
Section: Methodsmentioning
confidence: 99%
“…A atividade física além de melhorar a capacidade muscular, melhora na resistência, mobilidade articular, agilidade, velocidade e a coordenação em geral (Katzer et al, 2012). A atividade física regular aumenta o nível de aptidão física e a autoconfiança, principalmente em pessoas com maior grau de incapacidade (Bim et al, 2021). Por muito tempo foi recomendado exercícios aeróbicos, pelos seus efeitos no sistema cardiovascular, e controle de doenças, além dos benefícios psicológicos .…”
Section: A Coordenação Motora E a Atividade Física Para O Idosounclassified
“…Currently, numerous scientific studies confirm that the regular practice of physical activity (PA) brings significant benefits to health, both physiologically, mentally and socially, being considered one of the essential habits for the adoption of an active and healthy lifestyle (R. H. Bim et al, 2022;Ricardo Henrique Bim et al, 2021;Binder et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%